First complete mitogenomes of Diamesinae, Orthocladiinae, Prodiamesinae, Tanypodinae (Diptera: Chironomidae) and their implication in phylogenetics - Zheng, Chen-Guang; Zhu, Xiu-Xiu; Yan, Li-Ping; Yao, Yuan; Bu, Wen-Jun; Wang, Xin-Hua; Lin, Xiao-Long (PeerJ (San Francisco, CA), 2021)
The mitochondrial genome (mitogenome) has been extensively used for phylogenetic and evolutionary analysis in Diptera, but the study of mitogenome is still scarce in the family Chironomidae. Here, the first complete mitochondrial genomes of four Chironomid species representing Diamesinae, Orthocladiinae, Prodiamesinae and Tanypodinae are presented. Coupled with published mitogenomes of two, a comparative mitochondrial genomic analysis between six subfamilies of Chironomidae was carried out. Mitogenomes of Chironomidae are conserved in structure, each contains 37 typical genes and a control region, and all genes arrange the same gene order as the ancestral insect mitogenome. Nucleotide composition is highly biased, the control region displayed the highest A + T content. All protein coding genes are under purifying selection, and the ATP8 evolves at the fastest rate. In addition, the phylogenetic analysis covering six subfamilies within Chironomidae was conducted. The monophyly of Chironomidae is strongly supported. However, the topology of six subfamilies based on mitogenomes in this study is inconsistent with previous morphological and molecular studies. This may be due to the high mutation rate of the mitochondrial genetic markers within Chironomidae. Our results indicate that mitogenomes showed poor signals in phylogenetic reconstructions at the subfamily level of Chironomidae.